2011
DOI: 10.1186/1745-6215-12-19
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial examining Iyengar yoga for young adults with rheumatoid arthritis: a study protocol

Abstract: BackgroundRheumatoid arthritis is a chronic, disabling disease that can compromise mobility, daily functioning, and health-related quality of life, especially in older adolescents and young adults. In this project, we will compare a standardized Iyengar yoga program for young people with rheumatoid arthritis to a standard care wait-list control condition.Methods/DesignSeventy rheumatoid arthritis patients aged 16-35 years will be randomized into either the 6-week Iyengar yoga program (12 - 1.5 hour sessions tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Yoga aims to enhance participants' compassionate understanding of their health, enabling a nonjudgmental perception of pain without avoidance or social withdrawal. 40 Pain acceptance can also change patients' perspectives: Current study participants saw yoga as positive, even if it did not make them pain free.…”
Section: Acceptancementioning
confidence: 95%
“…Yoga aims to enhance participants' compassionate understanding of their health, enabling a nonjudgmental perception of pain without avoidance or social withdrawal. 40 Pain acceptance can also change patients' perspectives: Current study participants saw yoga as positive, even if it did not make them pain free.…”
Section: Acceptancementioning
confidence: 95%
“…Most yoga studies lack a manualized intervention where poses for the study are shown so the study could be replicated, even with individualized adjustments based on participant's needs during the sessions [ 248 ]. Additional studies should include mechanisms and outcomes [ 249 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…If they indicate interest in the study, an eligibility screening interview will be conducted during the telephone call, with pre-defined inclusion and exclusion criteria questions based on previous yoga and musculoskeletal research (Table 1). [35][36][37] As pain and sleep disturbance are main secondary outcomes of interest, potential participants must verbally self-report average pain during the past month §3 on a 10-point numerical rating scale and sleep disturbance equivalent to .30 minutes at night. Participants will not be informed of these minimum inclusion levels before being asked to rate them.…”
Section: Recruitment Procedures and Baseline Assessmentmentioning
confidence: 99%